2021
DOI: 10.3390/genes12020253
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Sparing Mastectomy as a Risk-Reducing Procedure for BRCA-Mutated Patients

Abstract: Growing numbers of asymptomatic women who become aware of carrying a breast cancer gene mutation (BRCA) mutation are choosing to undergo risk-reducing bilateral mastectomies with immediate breast reconstruction. We reviewed the literature with the aim of assessing the oncological safety of nipple-sparing mastectomy (NSM) as a risk-reduction procedure in BRCA-mutated patients. Nine studies reporting on the incidence of primary breast cancer post NSM in asymptomatic BRCA mutated patients undergoing risk-reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…Indeed, Muller et al recently underlined the extremely low risk of cancer development following breast risk-reducing surgery as follows: specifically, out of 3716 cases of prophylactic NSMs, only 9 cases (0.2%) of BC exterior to the nipple-areola complex (NAC) and 1 case (0.004%) of BC within the NAC were reported [60]. To date, NSM appears to be a safe risk-reduction procedure for BRCA mutation carriers from an oncological point of view, as highlighted in a recent literature review, which reported low rates of new BCs, low rates of postoperative complications, and high levels of satisfaction and postoperative quality of life [61].…”
Section: Risk-reducing Surgical Strategy In High Risk Women: Conserva...mentioning
confidence: 99%
“…Indeed, Muller et al recently underlined the extremely low risk of cancer development following breast risk-reducing surgery as follows: specifically, out of 3716 cases of prophylactic NSMs, only 9 cases (0.2%) of BC exterior to the nipple-areola complex (NAC) and 1 case (0.004%) of BC within the NAC were reported [60]. To date, NSM appears to be a safe risk-reduction procedure for BRCA mutation carriers from an oncological point of view, as highlighted in a recent literature review, which reported low rates of new BCs, low rates of postoperative complications, and high levels of satisfaction and postoperative quality of life [61].…”
Section: Risk-reducing Surgical Strategy In High Risk Women: Conserva...mentioning
confidence: 99%
“…The choice of nipple-sparing mastectomy (NSM) versus simple mastectomy is an individualized decision that requires shared decision-making between the surgeon and the patient. A recent review of NSM in BRCA1/2 mutation carriers reported that NSM is a safe option for RRM, with low rates of new breast cancer on the side of prophylactic surgery and postoperative complications 15. There is no benefit to adjunctive chemoprevention after risk-reducing surgery and no compelling evidence exists to support continued surveillance with mammography or MRI after RRM.…”
Section: Prevention and Risk-reducing Strategies For Breast Cancer In...mentioning
confidence: 99%
“…This has been the largest series of prophylactic NSM in BRCA carriers in the literature to date and, although follow-up remains short, the cumulative evidence supports NSM as an appropriate risk-reducing procedure for patients with genetic variants. A review by Lewis et al and Rocco et al discussed and demonstrated the safety of NSM in genetic variant carriers [ 79 , 80 ].…”
Section: Prophylactic Surgerymentioning
confidence: 99%